Stability of Impulsive Neural Networks with Time-Varying and Distributed Delays - Qi Luo; Xinjie Miao; Qian Wei; Zhengxin Zhou (Abstract and Applied Analysis)
This work is devoted to investigating the stability of impulsive cellular neural networks with time-varying and distributed delays. We use the new method of fixed point theory to obtain some new and concise sufficient conditions to ensure the existence and uniqueness of solution and the global exponential stability of trivial equilibrium. The presented algebraic criteria are easily checked and do not require the differentiability of delays.